10. URVEY ON THE RELATIONSHIP BETWEEN TRADITIONAL MEDICINE SYNDROMES IN PEDIATRIC PATIENTS UNDER 5 YEARS OLD WITH ACUTE BRONCHIAL ASTHMA AND THE CLASSIFICATION OF ACUTE ASTHMA ATTACKS ACCORDING TO GINA (Vietnam Journal of Community Medicine, 2025)
Objectives: Survey on the prevalence of traditional medicine syndromes in pediatric patients under 5 years old during asthma attacks, along with the distribution of acute bronchial asthma severity grades according to the Global Initiative for Asthma (GINA) 2023, and determination of their correlation.Methods: A cross-sectional analytical study conducted from December 2024 to April 2025, randomly selecting all pediatric patients with acute asthma attacks diagnosed according to GINA 2023 criteria whose parents consented to participate, with data collected through structured questionnaires.Results: A total of 162 pediatric patients with acute bronchial asthma were surveyed. According to the GINA 2023 classification, the majority had mild asthma (93.8%), while the remainder had severe asthma (6.2%). Among the traditional medicine syndromes during asthma attacks, the Wind-Cold invading the Lung predominated (73.5%), followed by wind-heat invading the lung (26.5%). There was a statistically significant association between the traditional medicine syndromes and the severity classification of acute bronchial asthma according to GINA 2023 (p < 0.05).Conclusions: Severe asthma exacerbations accounted for a low proportion according to GINA 2023 classification. Wind-Cold invading the Lung was the most common traditional medicine syndrome. The study preliminarily concluded that traditional medicine syndromes during acute asthma attacks are related to the severity levels of acute asthma exacerbations according to modern medical classifications.
Keywords: Bronchial asthma, children, traditional medicine, GINA.